Cardiac Function After Cardiotoxic Treatments for Childhood Cancer—Left Ventricular Longitudinal Strain in Screening - Niemelä, Jussi; Ylänen, Kaisa; Suominen, Anu; Pushparajah, Kuberan; Mathur, Sujeev; Sarkola, Taisto; Jahnukainen, Kirsi; Eerola, Anneli; Poutanen, Tuija; Vettenranta, Kim; Ojala, Tiina (Frontiers in Cardiovascular Medicine, 2021)
Background: The majority of childhood cancer survivors (CCSs) have been exposed to cardiotoxic treatments and often present with modifiable cardiovascular risk factors. Our aim was to evaluate the value of left ventricular (LV) longitudinal strain for increasing the sensitivity of cardiac dysfunction detection among CCSs. Methods: We combined two national cohorts: neuroblastoma and other childhood cancer survivors treated with anthracyclines. The final data consisted of 90 long-term CCSs exposed to anthracyclines and/or high-dose chemotherapy with autologous stem cell rescue and followed up for > 5 years and their controls (n = 86). LV longitudinal strain was assessed with speckle tracking (Qlab) and LV ejection fraction (EF) by three-dimensional echocardiography (3DE). Results: Of the CCSs, 11% (10/90) had abnormal LV longitudinal strain (i.e., < -17.5%); of those, 70% (7/10) had normal 3DE LV EF. Multivariable linear model analysis demonstrated that follow-up time (p = 0.027), sex (p = 0.020), and BMI (p = 0.002) were significantly associated with LV longitudinal strain. Conversely, cardiac risk group, hypertension, age, cumulative anthracycline dose or exposure to chest radiation were not. Conclusion: LV longitudinal strain is a more sensitive method than LV EF for the detection of cardiac dysfunction among CCSs. Therefore, LV longitudinal strain should be added to the screening panel, especially for those with modifiable cardiovascular risk factors.